2005
DOI: 10.1021/ja054170t
|View full text |Cite
|
Sign up to set email alerts
|

Nonperfect Synchronization of Reaction Center Rehybridization in the Transition State of the Hydride Transfer Catalyzed by Dihydrofolate Reductase

Abstract: It has been suggested that the magnitudes of secondary kinetic isotope effects (2 degrees KIEs) of enzyme-catalyzed reactions are an indicator of the extent of reaction-center rehybridization at the transition state. A 2 degrees KIE value close to the corresponding secondary equilibrium isotope effects (2 degrees EIE) is conventionally interpreted as indicating a late transition state that resembles the final product. The reliability of using this criterion to infer the structure of the transition state is exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
109
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(120 citation statements)
references
References 84 publications
11
109
0
Order By: Relevance
“…This empirically parameterized model quantitatively replicates all of the 2°KIEs in the forward and reverse directions, as well as their mSSEs, and the LFER findings. The model also indicates an asynchronized hybridization for the donor and acceptor carbons, which was first identified for dihydrofolate reductase (DHFR) by QM/MM calculations (33). Finally, in accordance with the ensemble-averaged variational transition state theory (VTST) results from Truhlar, Gao, and co-workers (24,25), the model supports the recently articulated hypothesis that the inflated mSSEs reported for many ADHs since 1989 result from deflated 2°D/T KIEs because of the shorter donor-acceptor distance (DAD) required for D transfer (1,34).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…This empirically parameterized model quantitatively replicates all of the 2°KIEs in the forward and reverse directions, as well as their mSSEs, and the LFER findings. The model also indicates an asynchronized hybridization for the donor and acceptor carbons, which was first identified for dihydrofolate reductase (DHFR) by QM/MM calculations (33). Finally, in accordance with the ensemble-averaged variational transition state theory (VTST) results from Truhlar, Gao, and co-workers (24,25), the model supports the recently articulated hypothesis that the inflated mSSEs reported for many ADHs since 1989 result from deflated 2°D/T KIEs because of the shorter donor-acceptor distance (DAD) required for D transfer (1,34).…”
mentioning
confidence: 65%
“…3 mirrors the VTST treatment (39) that has been quite successful in modeling enzymatic reactions that involve H tunneling (24,25,33). In these models, the enzyme facilitates tunneling of the transferred particle by creating energetic degeneracy between a donor and acceptor state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of coupled motion for both enzymes agrees with a similar nature of the H-transfer mechanism, but reduced 2° KIEs indicate some differences in the system's vibrational states, which could be in agreement with different rearrangements of the potential surface close to the transition state. Interestingly, a more rigorous MM/QM study of the 2° KIEs for the wild type ecDHFR indicated non-synchronized hybridization of the donor and acceptor carbons and slightly associative transition state (91). A similar study of the G121V mutant is under way, and it's findings may shed light on the differences between the transition state ensembles of the wild type and G121V ecDHFRs.…”
Section: "Marcus Like" Models (Environmentally Coupled Tunneling)mentioning
confidence: 86%
“…[512][513][514] Alternatively, for H transfer, when the donor and acceptor experience changes of the hybridization states, recent studies emphasized the usefulness of employing the change of one or both hybridization states as the DRC. 408 Any combination of bond distances, bond angles, or torsion angles is called a valence coordinate, whereas quantities based on diabatic potentials or electrostatic fields that depend on solvent or bath coordinates are often called collective solvent coordinates. Valence coordinates are also called geometrical coordinates.…”
Section: Ensemble-averaged Variational Transition State Theory With Mmentioning
confidence: 99%